W stronę badań słowiańskich kontekstów staropolskich apokryfów (2). Sposoby wprowadzania przytoczeń w Životě Krista Pána oraz Żywocie Pana Jezu Krysta Baltazara Opeca - Borowiec, Karolina (Slavia Occidentalis, 2016)
The aim of the article is to observe the similarities and differences concerning the formation of text by the writers of two Slavic Biblical-apocryphal narrations based on the analyses of the means of introduction of quotations in the Czech Život Krista Pána and in the Polish Żywot Pana Jezu Krysta by Baltazar Opec. The author of the article demonstrates that the texts were written at a similar stage of development of both vernacular languages and, consequently, they include structures at different levels of complexity – indirect speech coexists with direct speech and intermediate forms. The author indicates the differences and similarities in the way the metatext is constructed. For example, she contends that the author of ŽKP used direct speech much more often, introduced quotations serving as a commentary on specific events differently (e.g., from the Bible or Church Fathers), used different patterns when introducing the utterances of the protagonists of the story. Also, the author of the article shows that the quotations intertwined in the story Żywot Pana Jezu Krysta were more expensively modified in comparison to ŽKP. Moreover, the repertoire of structures used for the inclusion of reported speech into the main narration is richer in the Polish text.